Archaeology, History, Philosophy and Heritage
XX, 426 p. 54 illus., 37 illus. in color.
Keywords: This festschrift volume celebrates Tim Murray’s significant and wide-ranging contribution to archaeological thought and practice. It includes 27 papers by Tim Murray’s colleagues, research collaborators and students—former and current. Together these comprise a substantive and reflective contribution to Archaeology, History, Philosophy and Cultural Heritage in Australia, Oceania, China, India, the United Kingdom, Northern Europe, and North America. The collected papers in this volume tie together Murray’s research into the history (or historiography) of archaeological thought, and his commitment to understanding the material culture of the past to ‘write history’. They provide a cross-section of philosophical enquiries and substantive research: from epistemological studies of shared lexicons and important debates in the history of archaeological thought, to the minutae of material culture studies. Several papers explcitly and implicitly explore one of Murray’s great interests: the role of heritage preservation in our exploration of the past, including dedicated tertiary training programs for Indigenous Australians to manage, research and protect their own Country. The book is divided into four parts: History, Archaeology, Philosophy and Heritage, offering an interdisciplinary approach to the study of the past. This volume would be of interest to archaeologists, historians, philosophers of archaeology, and heritage scholars.